2019
DOI: 10.3208/jgssp.v07.024
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanism of loess landslide induced by chlorine salt in Heifangtai terran

Abstract: It is well known that water content is the key factor affecting the loess strength. In arid and semi-arid regions, the salt content in pore solution of loess is relatively high. Rainfall or irrigation can change the water content of loess and induce geological disasters such as loess landslide and loess mud flow. In this paper, Heifangtai, Gansu Province, is chosen as the study site, where is the most typical place of loess landslides. The occurrence of loess landslides is closely related to water, salt. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Rainfall, irrigation, earthquakes, and human activities are considered the main factors triggering loess landslides [13][14][15][16][17][18]. For example, in August 1955, a loess landslide with a volume of 3 × 107 m 3 occurred in Wolongsi of Baoji, Shaanxi Province, destroying a railroad, and a landslide occurred again at this location in 1971, killing 28 people [19].…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall, irrigation, earthquakes, and human activities are considered the main factors triggering loess landslides [13][14][15][16][17][18]. For example, in August 1955, a loess landslide with a volume of 3 × 107 m 3 occurred in Wolongsi of Baoji, Shaanxi Province, destroying a railroad, and a landslide occurred again at this location in 1971, killing 28 people [19].…”
Section: Introductionmentioning
confidence: 99%
“…In one hand, it increases the weight of the slope and on the other hand makes the soil more resistant. The shear strength is reduced (Yang et al 2010). By fitting the changes of soil strength parameters under different normal stresses, the shear strength envelope of natural soil and artificially intervention saturated landslide soil was obtained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the NaCl concentration can have a fundamental influence on the shear behavior of loess soils [19,22,25]. Fan et al, [17] has reported that the shear strength of saturated loess soils increases as the NaCl concentration increases, while some other researchers have concluded that the increase of NaCl concentration leads to the reduction in shear strength of saturated loess soils [22,45]. However, we found that both the peak strength and residual strength increase as the NaCl concentration increases up to a specific value (See Figures 6 and 7).…”
Section: The Peak Shear Strength and Residual Strengthmentioning
confidence: 99%